Carbazole-substituted metallo-phthalocyanines: Synthesis, electrochemical, and spectroelectrochemical properties - İpsiz, Özlem; Yenilmez, H. Yasemin; Kaya, Kerem; Koca, Atıf; Bayır, Zehra Altuntaş (Elsevier BV, 2016)
Abstract The syntheses of tetrasubstituted metallo-phthalocyanines (cobalt, zinc, and manganese) bearing four 9H-carbazole-9-ethoxy units have been reported. All of the synthesised compounds have been characterised by using FT-IR, UV–vis, 1 H NMR, and MALDI-TOF/MS spectroscopic data. The aggregation behaviours of the newly synthesised compounds were investigated in different concentrations. Electrochemical and spectroelectrochemical characterisation of Cl-MnPc was performed in DMF. Two metal-based reductions followed a Pc ring-based reduction. An irreversible Pc ring-based oxidation could only be detected with square wave voltammetry. In situ spectroelectrochemical and electrocolorimetric measurements were performed in order to determine the colours and spectra of the electrogenerated species of the complex.